2006
DOI: 10.1063/1.2229937
|View full text |Cite
|
Sign up to set email alerts
|

Capillary condensation and quantum vacuum effects on the pull-in voltage of electrostatic switches with self-affine rough plates

Abstract: Link to publication in University of Groningen/UMCG research database Citation for published version (APA): Palasantzas, G. (2006). Capillary condensation and quantum vacuum effects on the pull-in voltage of electrostatic switches with self-affine rough plates. Journal of Applied Physics, 100(5), art. -054503.[054503]. DOI: 10.1063/1.2229937 Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Interestingly, (16) . These results may be summarized in a regime diagram illustrating the parameter ranges for which each of the two contact (or adhesion) transitions occur -see figure 5, bottom.…”
Section: Numerical Procedures and Resultsmentioning
confidence: 99%
“…Interestingly, (16) . These results may be summarized in a regime diagram illustrating the parameter ranges for which each of the two contact (or adhesion) transitions occur -see figure 5, bottom.…”
Section: Numerical Procedures and Resultsmentioning
confidence: 99%
“…14,16 Recently, we studied the influence of capillary forces in combination with electrostatic and quantum vacuum generated forces on the pull-in voltage of microswitches having self-affine rough surfaces. 19 It was shown that the attractive capillary force decreases more the effective electrostatic pull-in voltage when the plate surfaces are rougher. The latter corresponds to smaller roughness exponents H ͑0 Ͻ H Ͻ 1, which characterize short wavelength roughness͒ and/or larger long wavelength roughness ratios w / with w the root-mean-square ͑rms͒ roughness amplitude and the in-plane correlation length.…”
Section: Introductionmentioning
confidence: 99%
“…The latter corresponds to smaller roughness exponents H ͑0 Ͻ H Ͻ 1, which characterize short wavelength roughness͒ and/or larger long wavelength roughness ratios w / with w the root-mean-square ͑rms͒ roughness amplitude and the in-plane correlation length. 19 Therefore, since capillary forces can strongly influence the operation of microswitches, the influence of the capillary meniscus contact angle on the pull-in potential will be further investigated. Indeed, up to now we have not presented any detailed investigation of the influence of the contact angle on pull-in characteristics for rough plate surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Recent studies for switches with rough plates have shown that random selfaffine roughness, which often occurs during nonequilibrium film growth, strongly influence pull-in parameters of microswitches in presence of electrostatic, Casimir, and capillary forces. 18,19 Besides EM vacuum fluctuations which induce an attractive Casimir force, 15 Larraza 20 transferred this idea into acoustics and measured the force between two parallel plates in an external sound field with a bandwidth from 5 to 20 kHz. 20 In the space between the two plates, lowerfrequency modes were suppressed leading to an attractive force.…”
Section: Introductionmentioning
confidence: 99%